Effect of grinding damage on cutting force and ductile machining during single grain scratching of monocrystalline silicon. (15th November 2022) - Li, Ming; Guo, Xiaoguang; Dai, Siyang; Yuan, Song; Ma, Jianli; Liu, Fumin; Zhang, Lemin; Guo, Dongming; Zhou, Ping
Abstract: Understanding the initiating and suppression mechanisms of existing defects are the key to optimizing the ultra-precision grinding process of hard and brittle materials. This paper discusses the effects of grinding damage on material removal mechanism from the perspectives of residual scratch depth, scratch morphology and normal scratching force, through conducting the contrast variable-depth nano-scratch experiment on polished and ground monocrystalline silicon and establishing the single grain scratching Smoothed Particle Hydrodynamics (SPH) model. The experimental and simulation results show that radial crack on ground silicon surface is almost invisible due to the existence of grinding marks, which indicates that it is difficult to judge the ductile brittle transition (DBT) point by the traditional method of observing cracks. With the increase of penetration depth, pop-in will occur in the residual scratch depth of polished and ground silicon, indicating that the material removal mode has transformed, which provides an important basis for judging the DBT point. The DBT critical normal scratching force (38.93 mN) and residual scratch depth (−0.14 μm) of ground silicon are much higher than those of polished silicon, implying ground silicon is easier to achieve ductile processing. Meanwhile, when the penetration depth is the same, compared to polished silicon, the normal scratching force of ground silicon is generally larger. Finally, a single grain scratching SPH model of pre-stressed silicon is established. And the simulated phenomenon and conclusions are consistent with the experiment, which proves that the surface compressive stress is an important factor that causes the removal characteristics of ground silicon to be different from polished silicon. This study provides a theoretical basis for understanding the ultra-precision grinding removal mechanism of hard and brittle materials.